Geopolitik Indonesia sebagai negara maritim dalam menjaga keamanan laut - rafiuddin, Ahmad rafi (Maliki Interdisciplinary Journal, 2026)
Indonesia’s geopolitics as a maritime state constitutes a crucial strategic aspect in maintaining national sovereignty and security. As the world’s largest archipelagic country, Indonesia is geographically positioned between Asia and Australia, and lies between the Indian Ocean and the Pacific Ocean, making it a vital route for international trade and shipping. This study aims to analyze Indonesia’s geopolitical concept based on Wawasan Nusantara, identify maritime security threats and challenges, and examine strategies and policies implemented to maintain stability in its territorial waters. This research employs a qualitative approach using literature review from various academic and policy sources. The findings indicate that Indonesia faces multiple maritime threats, including illegal fishing, smuggling, human trafficking, and violations of maritime boundaries. To address these challenges, the government has strengthened the roles of Indonesian Navy and Indonesian Maritime Security Agency, while also adhering to international legal frameworks such as the United Nations Convention on the Law of the Sea. Additional strategies include enhancing international cooperation, modernizing defense equipment, and utilizing maritime surveillance technology. Therefore, strengthening Indonesia’s maritime geopolitics requires an integrated and sustainable approach to safeguard sovereignty, security, and national prosperity.